The Virtual Kitchen Challenge: preliminary data from a novel virtual reality test of mild difficulties in everyday functioning. Issue 6 (2nd November 2019) - Giovannetti, Tania; Yamaguchi, Takehiko; Roll, Emily; Harada, Tetsuya; Rycroft, Sarah Seligman; Divers, Ross; Hulswit, Jacob; Tan, Chiu C.; Matchanova, Anastasia; Ham, Lillian; Hackett, Katherine; Mis, Rachel
ABSTRACT: Background: Efficient, objective measures of mild functional difficulties are lacking. Preliminary data from a novel, non-immersive virtual reality, performance-based task (Virtual Kitchen Challenge; VKC) were obtained to address this gap. Methods: 14 older and 21 younger adults completed cognitive tests and two everyday tasks (breakfast, lunch) in the VKC with virtual objects and a touch-screen and in the Real Kitchen with real objects (order counterbalanced). Automated performance measures were obtained from the VKC program and human coders scored VKC and Real Kitchen videos for errors. Results: Older adults made more errors than younger adults on the VKC and Real Kitchen, with similar error patterns across measures. VKC automated measures were significantly related to measures from human coders, performance on the Real Kitchen, and cognitive test scores. Conclusion: The VKC is a valid and highly efficient performance-based measure of subtle functional difficulties with great potential for future clinical and research applications.